Empowerment of Pokdarwis (Tourism Awareness Groups) in Developing Ecotourism Sarasah Waterfall Banda Lasuang, Lubuk Kilangan Sub-District, Padang City - Awalina, Rahmi; Hasbullah, Hasbullah (Andalasian International Journal of Social and Entrepreneurial Development, 2024)
This service aims to provide assistance to members of the tourism awareness group (POKDARWIS) in Batu Gadang Village, Lubuk Kilangan District, Padang City regarding the management and management of ecotourism, which includes the concept of ecotourism, governance, physical maintenance of ecotourism, promotion and analysis of the potential of community social resources. This service begins with social analysis and then continues with the Appreciative Inquiry method which includes the Discover, Dream, Design, and Destiny stages. The targets of this community service activity are members of the Batu Gadang Urban Village tourism awareness group (POKDARWIS) who are actively involved in the management of nature tourism villages. Tourism Awareness Groups are given socialization, training, assistance and empowerment regarding the management and management of ecotourism. The results of this dedication show the excellent enthusiasm and motivation of the tourism awareness group in planning ecotourism management, developing ecotourism through fulfilling facilities and infrastructure according to needs, maintaining tourism assets, and promoting and empowering the economy of the community around tourist attractions